PHYSICAL EDUCATION TEACHER KNOWLEDGE LEVEL ABOUT RULES OF BASKETBALL GAME IN JOMBANG DISTRICT SENIOR HIGH SCHOOL - Arnaz Anggoro Saputro; Guntum Budi Prasetyo (PHEDHERAL, 2021)
The purpose of this study was to determine how high the level of knowledge of physical education teachers on the rules of basketball games in high schools in Jombang district. The research method used a descriptive research approach by surveying 18 physical education teachers in 12 high school schools in Jombang District, Jombang Regency. East Java. The data collection technique is done by using a questionnaire that utilizes the google form application so that the questionnaire can be filled online. The data analysis used is descriptive with the results of the assessment of all teachers carried out with the same tool which will be made into 5 categories, namely very high, high , moderate, low and very low categories. The results showed the level of knowledge of the physical education teachers on the rules of basketball games in high schools in Jombang District, namely 5 respondents (27.78%) were in the very high category, 4 respondents (22.22%) were in the high category, 5 respondents ( 27.78%) is in the medium category, 1 respondent (5.55%) is in the low category, and 3 respondents (16.67%) are in the Very low category, and when viewed from the mean (Mean) in the overall results of respondents with a value of 25.61, this value is also in the "medium" category. Thus it can be concluded that physical education teachers in SMA in Jombang District have a fairly good level of knowledge of the rules of the basketball game.